EUS-guided fine-needle core liver biopsy with a modified one-pass, one-actuation wet suction technique comparing two types of EUS core needles - Nieto, Jose; Dawod, Enad; Deshmukh, Ameya; Penn, Eli; Adler, Douglas; Saab, Sammy (Endoscopy International Open, 2020)
Background and study aims We compared the diagnostic yield and specimen adequacy in EUS-guided parenchymal biopsies between two types of EUS 19 G core needles.Patients and methods This is a retrospective study of 420 patients at two tertiary medical centers in Florida with unexplained abnormal liver associated tests were referred for EUS evaluation of biliary obstruction and pancreatic pathology. EUS-guided liver biopsy (EUS-LB) was performed at the same session after biliary obstruction was excluded. We compared intact specimen length (ISL), total specimen length (TSL), complete portal triads (CPT) and adverse events (AE). Welch’s T and Tukey tests were used for ISL, TSL and CPT.Results A total of 210 patients underwent EUS-LB using a Franseen needle, 210 patients using a fork-tip needle. Median patient age was 52 years (15.63) and 238 (56.7 %) were female. The fork-tip needle had a mean ISL of 2.7 (1.1 SD) cm, TSL of 6 cm (2.1 SD), and mean 19.5 CPT (8.5 SD) Abdominal pain occurred in 35 patients (17 %) post-procedure and was managed with supportive care. Two patients required intravenous (IV) narcotic administration. Subcapsular hematomas occurred in 1 (0.5 %) patients. The Franseen needle had a mean ISL of 3.1 cm (1.3 SD), TSL of 6.5 cm (2.6 SD), and mean of 24 CPT (8.8 SD). Abdominal pain occurred in four patients (2 %) post-procedure, which resolved in all patients after IV narcotic administration. Subcapsular hematomas occurred in 1 (0.5 %) and bile leak in 1(0.4 %) patients.Conclusions Use of the Franseen needle resulted in better liver core samples than that obtained with a fork-tip needle.